2015
DOI: 10.4236/jct.2015.61008
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Using Novel Zinc Phthalocyanine Derivatives and a Diode Laser for Superficial Tumors in Experimental Animals

Abstract: Photodynamictherapy (PDT) using a photo sensitizing agent and several light sources has been shown to have nonspecific and noninvasive effects on superficial cancers. Phthalocyanine (Pc) derivatives as novel photosensitizers, trifluoroethoxy-coatedzinc Pcconjugated with β-cyclodextrin (βCD-4TFEO-Pc) was synthesized and its photodynamic effect in vitro and in vivo was evaluated. βCD-4TFEO-Pc alone was completely non-cytotoxic even at high concentrations, and showed excellentphotodynamic effects in B16-F10 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Absorption, λ abs [nm], (A rel [a] ), {fwhm} [cm À 1 ] Fluorescence emission [b] Stokes shift Soret phthalocyanine, [31] which were evaluated by mouse B16 melanoma cells.…”
Section: Compoundmentioning
confidence: 99%
“…Absorption, λ abs [nm], (A rel [a] ), {fwhm} [cm À 1 ] Fluorescence emission [b] Stokes shift Soret phthalocyanine, [31] which were evaluated by mouse B16 melanoma cells.…”
Section: Compoundmentioning
confidence: 99%
“…Pc also has promising use in chemical sensor as shown by Braik et al [35] where they used Co(II) phthalocyanine acrylate polymer for perchlorate anion detection [35]. In the field of medicine, derivatives of pc are now being used in photodynamic therapy of cancer as they show strong absorption in far red-light in the wavelength 600-800 nm [35,36]. Pc derivatives are a promising photosensitizer in fight of pathogenic microbes.…”
Section: Applications Of Phthalocyaninementioning
confidence: 99%
“…After that TFEO-ZnPc/cyclodextrin conjugates 18 were reported under similar conditions ( Scheme 7 ) [ 100 ]. That study revealed that cyclodextrin-linked TFEO-Pcs have a non-aggregation property and sufficient water solubility, similar to the deoxyribonucleoside conjugates.…”
Section: Reviewmentioning
confidence: 99%